2018
DOI: 10.1111/ijac.12864
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of dense, fine‐grained hexagonal barium ferrite ceramics by two‐step sintering process

Abstract: Two-step sintering (TSS) process has been used to fabricate hexagonal barium ferrite (BaFe 12 O 19 , BaM) ceramics with high density and fine grain size. The densification, microstructure, and magnetic properties were investigated. The sample prepared by the TSS process with the first-step sintering temperature of 1325°C, the second-step sintering temperature of 1300°C, and holding time of 20 hours has a density of 98.01 AE 0.25% of the theoretical density (5.29 g/cm 3 ) and exhibits a uniform microstructure w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…In addition, it can be found that the effect of increasing the same fracture surface energy at high temperatures is better than that at normal temperatures. Studies have shown that increasing sintering temperature 26 or adopting a two‐step sintering process 27 can reduce the porosity of materials, improve the density of materials, and thus improve the fracture surface energy of materials.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, it can be found that the effect of increasing the same fracture surface energy at high temperatures is better than that at normal temperatures. Studies have shown that increasing sintering temperature 26 or adopting a two‐step sintering process 27 can reduce the porosity of materials, improve the density of materials, and thus improve the fracture surface energy of materials.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, as indicated in Figure 2, in the nitrogen environment, the prediction results of the two methods are again consistent with the experimental data at 1400°C, the experimental data in the nitrogen environment is much lower than the experimental data in Figure 1 in the air environment, which again confirms the above statement. Further, to facilitate comparison, the prediction results of Deng 20 , ACK 11 , and Marshall and Cox combined with TA B L E 2 Material parameters for different fiber-reinforced ceramic matrix composites (FRCMCs) 10,16,22,[25][26][27][28][29] 2 and 3. As indicated in Figure 3 that the prediction results of the models are in good agreement with the measurement results.…”
Section: Sic F /Rbsn Compositesmentioning
confidence: 99%
“…Polycrystalline samples of Y 3 Zn x Zr x Fe (5−2x) O 12 for x = 0.0, 0.05, 0.1, 0.15, 0.2, and 0.3 were prepared by solid-state reaction method 25,26 with powdered Y 2 O 3 (99.99%), ZrO 2 (99.99%), ZnO (99%), and Fe 2 O 3 (99.9%). The prepared starting materials according to the stoichiometric ratio were put into a planetary ball mill and well mixed with the anhydrous ethanol for 24 hours.…”
Section: Methodsmentioning
confidence: 99%
“…Internal metallic ions sites interaction in hexagonal crystalline structure of BaFe 12 O 19 could be responsible for its magnetic properties. Until now, several methods have been used to synthesize BaFe 12 O 19 nanomaterials such as co‐precipitation, glass crystallization, hydrothermal synthesis, sol‐gel techniques, etc 10‐13 . Cation substituting process is an effective tool for modification of magnetic and microwave properties of M‐type hexaferrite has been applied with the aid of various cations such as La‐Zn, 14 copper and cobalt, 15 Nd‐Co, 16 Pr‐Bi, 17 Ni, 18 Nd, 19 etc To the best of our knowledge, there has not been any report on evaluating the effect of Mg‐Zr substitution on the magnetic and microwave properties of BaFe 12 O 19 .…”
Section: Introductionmentioning
confidence: 99%